2022
DOI: 10.1002/solr.202200960
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Surface Hydroxyl and Released Interfacial Strain by Inserting CsF Anchor Interlayer for High‐Performance Perovskite Solar Cells

Abstract: Defects passivation strategy for the atop perovskite films is widely investigated, while the buried interface between the tin oxide electron transport layer and the perovskite active layer should gain more attention since the interfacial strains and surface hydroxyl are inevitable during the fabrication process which would affect the efficiency and stability of the fabricated perovskite devices. Herein, the CsF interlayer between SnO2 and perovskite film is adopted to release the interfacial strain and decreas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…where μ, ε, ε 0 , J, L, V app , V r , and V bi are carrier mobility, vacuum permittivity, the relative dielectric constant, current density, the thickness of films, applied voltage, voltage drop, and built-in voltage, respectively. 27,28 Similarly, compared with undoped PTAA films (2.01 × 10 −3 cm −2 V −1 S −1 ) and Li-doped PTAA films (3.95 × 10 −3 cm −2 V −1 S −1 ), 343FP-doped PTAA films (4.46 × 10 −3 cm −3 V −1 S −1 ) exhibited the highest mobility.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…where μ, ε, ε 0 , J, L, V app , V r , and V bi are carrier mobility, vacuum permittivity, the relative dielectric constant, current density, the thickness of films, applied voltage, voltage drop, and built-in voltage, respectively. 27,28 Similarly, compared with undoped PTAA films (2.01 × 10 −3 cm −2 V −1 S −1 ) and Li-doped PTAA films (3.95 × 10 −3 cm −2 V −1 S −1 ), 343FP-doped PTAA films (4.46 × 10 −3 cm −3 V −1 S −1 ) exhibited the highest mobility.…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of the undoped PTAA film, Li-doped PTAA film, and 343FP-doped PTAA film are 3.527 × 10 –6 , 5.923 × 10 –6 , and 6.708 × 10 –6 S·cm –1 , respectively. Figure b shows the corresponding mobility curve, and the electron mobility is calculated by the following equation: where μ, ε, ε 0 , J , L , V app , V r , and V bi are carrier mobility, vacuum permittivity, the relative dielectric constant, current density, the thickness of films, applied voltage, voltage drop, and built-in voltage, respectively. , Similarly, compared with undoped PTAA films (2.01 × 10 –3 cm –2 V –1 S –1 ) and Li-doped PTAA films (3.95 × 10 –3 cm –2 V –1 S –1 ), 343FP-doped PTAA films (4.46 × 10 –3 cm –3 V –1 S –1 ) exhibited the highest mobility. The results show that 343FP can indeed effectively improve the conductivity of the PTAA film and increase the efficiency of photogenerated carrier migration from the PSK layer to the HTL, which is consistent with the results of PL spectroscopy, proving the stronger PL quenching effect in the device.…”
Section: Resultsmentioning
confidence: 99%
“…The corresponding adjustment of the preparation technology is an important way to control this strain. [126][127][128] Zhao et al [129] did not use the traditional high-temperature annealing process, but grew the MAPbI 3 perovskite film at room temperature in a vacuum atmosphere for 3 days. The authors found no stress in these films, proving that temperature is the key factor for the lattice strain in the perovskite layer.…”
Section: Preparation Processmentioning
confidence: 99%
“…Low-temperature processed SnO 2 ETLs have been reported to deliver high device performance [14][15][16], even superior to that of their high-temperature processed counterparts [17,18]. Up to now, the main strategy for boosting the performance and stability of SnO 2 based devices has been to suppress energy loss within SnO 2 [19,20] or at the ETL/perovskite interface [21][22][23]. Doping is a direct and effective method of modifying the properties of SnO 2 , such as the conductivity and work function, which can facilitate electron extraction and transport [24].…”
Section: Introductionmentioning
confidence: 99%